The Importance of the Uzbek National Musical Heritage in the Education of Youth (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the Uzbek national musical heritage, the development of the traditional art of maqom, and promising projects. The magic of the "Shashmaqom" song, its pleasant freshness to the heart, and its positive impact on the spirituality of young people are analyzed.This study explores the significance of Uzbek national musical heritage, particularly the art of maqom, in shaping youth education. While numerous initiatives have been undertaken to preserve and promote maqom, a gap remains in integrating it systematically into the educational framework. This research employs a qualitative analysis of existing policies, cultural programs, and historical developments related to maqom. The findings indicate that maqom has a profound impact on students' cultural identity, emotional well-being, and artistic development. Results highlight the importance of national initiatives, such as the International Maqom Art Festival and academic research on maqom notation, in preserving this intangible heritage. The study emphasizes the need for a structured approach in incorporating maqom into music education curricula, enhancing its accessibility to younger generations. Strengthening institutional support, developing comprehensive educational programs, and fostering collaboration between musicians and educators are crucial for sustaining maqom as a vital part of Uzbekistan’s cultural legacy.